AN EXAMINATION OF THE CONCEPT AND CLASSIFICATIONS OF MAQAM IN THE HISTORICAL PROCESS (13th-20th CENTURIES) - Emre Akgün (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Classical Turkish music, which has been continuing to be fed with the Middle Ages Islamic world since the 10th century, owes its development to the pieces written by many theorists and composers, especially Fârâbî, İbn-î Sînâ, Safüyüddin Urmevî, Abdülkâdir Merâgî, Bedri Dilşad, Lâdikli Mehmed Çelebi, Abdülbâkî Nâsır Dede, Dimitri Cantemir, Rauf Yektâ. In these pieces, explanations are given on the concept of maqam, the formation of maqam, the factors affecting its formation (caesura, prepotent, course), and its classification. Especially in the pieces having been written since the fifteenth century, there is a distinction in the classification, with the word maqam being mentioned more frequently. In the research, it is aimed to investigate the change in the concept of maqam in Classical Turkish music in the historical process and to see the theoretical approaches of theorists and composers to the concept of maqam. The study, within the framework of maqam definitions and classifications, is limited to the period between the 13th and 20th centuries. In the research, it is seen that the fifteenth century was a transition period as a maqam expression style, and since this century, maqam narrations have been made with note and course focusing rather than quartets and quintuplets.